Tratamiento biológico de las infecciones piógenas agudas : Método de la "cavidad cerrada" - Dasso, Héctor (1937)
The author establishes in the foreground the difference which exist between a «puriform» exudate and a «purulent» exudate, demonstrating the extraordinary therapeutic value of the method of Mendez, in the treatment of acute pyogenic infectious. On recognizing that the «puriform» exudate by its composition is totally reabsorbable and that by its qualities is the curative agent of the inflammation, he sustaints, in accordance with the argentine biological theory — that it must be maintained in contact with the affected surfaces, that is to say, that the basis of the natural cure is represented by the contact of the specific haptinas with the antigen. For the formation of indispensable haptinas, in order to obtain the biological cure, the patient should be put in the right track, completing with the inyectiou of híiptinógeno corresponding to the infecting germs. This method of curation being called the «closed cavity». This method was patronized by Julio Méndez and published ten years before the appearance of the first works of Orr, demonstrating at the same time, that those curatives methods by ample evacuations (drainage), which are also bloody are completely anti-physiologic and non-productive, because they badly obtain the desired cure.